2020
DOI: 10.1002/jcla.23521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of circular RNA expression profiles of lung cancer in Xuanwei, China

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Ryo Uratani et al demonstrated the potential role of total serum miR-21, miR-29a and miR-92a in the early detection of colorectal adenomas and cancers [62]. CircRNAs and exosomal circRNAs have the potential diagnostic values for Gastrointestinal (GI) malignancies and lung cancer [63,64]. Nevertheless, the role of exosomal clinical correlation of plasma exosomal circRNAs in colorectal adenomas compared to the healthy control group based on the results of the RNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Ryo Uratani et al demonstrated the potential role of total serum miR-21, miR-29a and miR-92a in the early detection of colorectal adenomas and cancers [62]. CircRNAs and exosomal circRNAs have the potential diagnostic values for Gastrointestinal (GI) malignancies and lung cancer [63,64]. Nevertheless, the role of exosomal clinical correlation of plasma exosomal circRNAs in colorectal adenomas compared to the healthy control group based on the results of the RNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the circVDAC3 is overexpressed in colorectal cancer (CRC) tissues and inhibits tumour progression via the miR‐942‐5p/BATF2 axis 7 . Furthermore, circVDAC3 is also overexpressed in the plasma of CRC patients, and high levels have been detected in the tumour tissues of lung cancer patients in Xuanwei 8,9 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Furthermore, circVDAC3 is also overexpressed in the plasma of CRC patients, and high levels have been detected in the tumour tissues of lung cancer patients in Xuanwei. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…LUAD is the main pathological type of XWLC. In recent years, the molecular mechanisms underlying the Xuanwei LUAD have been widely reported by high throughput techniques [11][12][13]. These studies described differentially expressed molecules and pathway changes in tumor tissues and provided high potential research value for XWLC.…”
Section: Introductionmentioning
confidence: 99%